2022
DOI: 10.1109/tc.2022.3146509
|View full text |Cite
|
Sign up to set email alerts
|

FLiMS: a Fast Lightweight 2-way Merger for Sorting

Abstract: In this paper, we present FLiMS, a highly-efficient and simple parallel algorithm for merging two sorted lists residing in banked and/or wide memory. On FPGAs, its implementation uses fewer hardware resources than the state-of-the-art alternatives, due to the reduced number of comparators and elimination of redundant logic found on prior attempts. In combination with the distributed nature of the selector stage, a higher performance is achieved for the same amount of parallelism or higher. This is useful in ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To maximise efficiency, parallel algorithms need to match specific platforms. For example, merge trees are still considered in state-of-the-art sorters on FPGAs [4], [5], while on CPUs prominent algorithms include radix sort [6], quicksort [7] and others [8]. Memory use is not the only reason for this discrepancy, but still, the main outcome is that there are different parallel memory access patterns, which can benefit from different memory topologies.…”
Section: Introductionmentioning
confidence: 99%
“…To maximise efficiency, parallel algorithms need to match specific platforms. For example, merge trees are still considered in state-of-the-art sorters on FPGAs [4], [5], while on CPUs prominent algorithms include radix sort [6], quicksort [7] and others [8]. Memory use is not the only reason for this discrepancy, but still, the main outcome is that there are different parallel memory access patterns, which can benefit from different memory topologies.…”
Section: Introductionmentioning
confidence: 99%
“…Usui.et.al. (9) proposed a tree-based merge sorter for large-scale sorting and successfully implemented. It was observed that the performance was degraded for the data that are distorted.…”
Section: Introductionmentioning
confidence: 99%